Emotion and Reason in Constructing a Historical Narrative: Polybius' Strategy of Reader's Moral Engagement. - Kurpios, Marcin (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2019)
The article investigates Polybius’ of Megalopolis conception of emotional response of the reader of a historical narrative, and explores the implications of that conception for the structure of selected parts of the Histories. The argument falls into three parts. First, Polybius’ focus on two particular emotions (pity and anger), the notions of the reasons and purposes, and the implications of their moral qualification are analyzed. The narrative strategy of Polybius is put into theory on the basis of his methodological considerations scattered around the Histories (Pol. 2.56.13; 16; 3.6.73; 31.7–11). In the second part the theory is verified on a sample of an account from the Histories about the preliminaries to the Hannibalic War (Pol. 3.9–33). Itis demonstrated how the strategy of evoking appropriate emotions influences shaping of the narrative of the antecedent events of the War, and how anger and pity, as the pivotal feelings, drive the actions of both the sides of the story, i.e. the Romans and the Carthaginians.The chronological shifts, the position and the emphasis on particular elements in the narrative, plus Polybius’ interventions into it, are explained in terms of the expected emotional and moral impact of the scrutinized text on the prospective recipient. Further, it is argued that in Polybius the idea of the emotional component guiding human choices and actions combined with the expected emotional impact of the narrative on the reader provide the main lines for structuring the account. In this context, it is stressed that Polybius advocates an ethical rather than purely emotional, long-lasting rather than momentary effect of a historical narrative. The last part of the paper discusses the tradition in which such strategy should be situated. Marincola’s reading in terms of judicial rhetoric is questioned, and the originality of Polybius’ conception, taking the probable expectations of average readers into account, is put forward.
Keywords: Polybius